GUARDIANS CONCEPT IN QUR'AN PERSPECTIVE - Habibi Al Amin; Masrokhin Masrokhin; Khoirul Anwar (LPPM UNHASY, 2021)
This article is the result of library research. The direction of this research discussion is how the process of interpreting ahkam works in producing a variety of guardianship concepts. This article discusses the application of esoteric interpretations of Hanafi and Syafi'I fiqh in the practice of istinbath and istidlal. The data sources of this research are the verses of the Qur'an and reference books that discuss the Hanafi and Shafi'I interpretation methods, namely al-Umm by Imam Shafi'I and al-Mabsut by as-Shaukani. This study concludes several things related to the concept of guardianship in the Qur'an. First, the concept of guardianship in the Qur'an cannot be imposed equally between Shafi'iyah and Hanafiyah. This difference arises because there is no sarih lafad that refers to the meaning of guardianship in the Qur'an. Second, the concept of guardianship appears diverse because the priests of the schools use different esoteric fiqh approaches in understanding the verses and al-Sunnah. The esoteric approach to fiqh carried out by Hanafi and Shafi'I relies on the same istinbath and istidlal process but the data used are different. Keyword: concept, wali, qur'an Abstrak Artikel ini adalah hasil penelitian kepustakaan. Arah diskusi penelitian ini adalah bagaimana proses kerja tafsir ahkam dalam memproduksi keragaman konsep perwalian. Artikel ini mendiskusikan penerapan tafsir esoterik fiqih Hanafi dan Syafi’I dalam praktek istinbath dan istidlal. Sumber data penelitian ini adalah Ayat Al-Qur’an dan buku-buku referensi yang membahas metode tafsir Hanafi dan Syafi’I, yaitu al-Umm karya Imam Shafi’I dan al-Mabsut karya as-Shaukani. Penelitian ini menyimpulkan beberapa hal berkaitan dengan konsep perwalian dalam Al-Qur’an. Pertama, konsep perwalian dalam Al-Qur’an tidak dapat dipaksakan sama antara Shafi’iyah dan Hanafiyah Perbedaan ini muncul karena tidak ada lafad sarih yang menunjuk pengertian perwalian dalam Al-Qur’an. Kedua, konsep perwalian muncul beragam karena para imam mazhab menggunakan pendekatan esoterik fiqih yang berbeda-beda dalam memahami ayat-ayat dan al-Sunnah. Pendekatan esoterik fiqih yang dilakukan Hanafi dan Shafi’I bertumpu pada proses istinbath dan istidlal yang sama akan tetapi data yang digunakan berbeda Kata Kunci : konsep, wali, al-qur’an